Dampak Penggunaan Gawai pada Sosial Emosional Remaja Sekolah Asrama : Penelitian - Saputri, Nur Sholehah Dian; Gumelar, Fikri Arif (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Advances in technology have caused the use of gadgets to become more widespread among people, including teenagers. Various types of devices such as smartphones, tablets, and computers cause various impacts such as the influence on achievement, discipline, interest in learning, social interaction and communication, and adolescent emotions. The purpose of this study was to understand the impact of using gadgets on the social and emotional aspects of adolescents at SMAIT Al-Multazam 2 Linggajati. This descriptive qualitative research is conducted on teenagers at SMAIT Al-Multazam 2 Linggajati, a boarding-based school. Participants are 15 students who are active gadget users. The results of this study indicate that all adolescents who are participants are active users of devices (tablets). Some teenagers lack confidence in their physical condition. Participants can convey their strengths and weaknesses and are partly open with their peers about themselves. In facing unpleasant or angry situations, participants prefer to remain silent and divert to other things. From the presentation in this study, it can be concluded that the use of gadgets in boarding schools has an impact on adolescents' social emotionality.